Ultrasound Diagnosis of Cholecystitis and Cholelithiasis: A Study of Various Types and Complications for Better Management - Taalaibek Bekov, Jumabek Mamasaliev, Ertegin Baigashkaev, Tugolbai Tagaev (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Ultrasound examination plays a crucial role in diagnosing cholecystitis and cholelithiasis, but its reliability in predicting inflammation severity and distinguishing between acute and chronic cholecystitis remains contested. This study aimed to provide ultrasound examination of various types of cholecystitis and cholelithiasis. Materials and Methods: A total of 650 subjects, including 48 healthy controls and 602 patients who underwent surgery for acute, chronic, destructive cholecystitis, or cholelithiasis, were examined using a Siemens scanner. Ultrasonography parameters assessed blood flow in the branches and veins of the cystic artery using color Doppler scanning and pulsed-wave Doppler. Quantitative blood flow velocity indicators and angle-independent total peripheral resistance indices were examined. Results: Gallbladder length and area were significantly increased in acute, phlegmonous, and gangrenous inflammation compared to controls. Wall thickness exceeded 4–5 mm in acute and phlegmonous-gangrenous inflammation. Maximum systolic blood flow velocity in the cystic artery more than doubled in acute, phlegmonous, and gangrenous inflammation, while minimum systolic velocity showed no significant changes. Total peripheral resistance indices increased in chronic, phlegmonous, and gangrenous inflammation but remained within control values in acute inflammation. The control group showed no significant differences in ultrasonographic indicators across all age groups. Conclusion: These findings highlight the importance of comprehensive clinical assessment alongside ultrasound imaging for accurate diagnosis and management of cholecystitis and cholelithiasis.